The The Influence Of Funding And Investment Decision On The Value Of Companies Listed On Indonesian Stock Exchange (IDX) - Linda Puji Lestari; Achadyah Prabawati (Penerbit Jurnal Indonesia, 2024)
Company value is one of the determining aspects before investors decide to invest funds in a company. The increase in company value from year to year is the company's achievement in running its business. The aim of this research is to determine the simultaneous and partial relationship between funding decisions and investment decisions on the value of companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data collection techniques in this research are documentation and literature study methods. The analysis of this research is multiple linear regression using SPSS 26 as a statistical test tool. The result in this research are there is no simultaneous influence between funding decisions and investment decisions on company value, there is a partial influence between funding decisions on company value, and there is no partial influence between investment decisions on company value. By optimizing funding decisions and investment decisions, company value will be able to increase.